2015 Winter Simulation Conference (WSC) 2015
DOI: 10.1109/wsc.2015.7408272
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of Health Information Systems using ARIS modeling and discrete-event simulation

Abstract: Innovation and health-care funding reforms have contributed to the deployment of Information and Communication Technology (ICT) to improve patient care. Many health-care organizations considered the application of ICT as a crucial key to enhance health-care management. This paper aims at providing a global methodology to assess the organizational impact of high-level Health Information System (HIS) on patient pathway. We propose a performance evaluation for HIS using formal modeling with ARIS (Architecture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…4 Models [26,28,32,38] Pakistan [24], Brazil [25], Ireland [26], Tanzania [27], United Kingdom [28,40], Sub-Saharan Africa [29], Somalia [30], Australia [31], India [31], Portugal [32], United States of America [33], France [33,45], Canada [33,44], Cyprus [34], Iran [35,36 ], Columbia [37], Libya [39], Sweden [40] Asia Pacific [24], Latin America and the Caribbean [25,37], European [26,28,[32][33][34]40], African Region [27,29,30,39], Asia Pacific [31], North America [33,44], Middle East and North Africa [31,35,36] Multilevel 6 Frameworks [45][46][47]…”
Section: Microlevelmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Models [26,28,32,38] Pakistan [24], Brazil [25], Ireland [26], Tanzania [27], United Kingdom [28,40], Sub-Saharan Africa [29], Somalia [30], Australia [31], India [31], Portugal [32], United States of America [33], France [33,45], Canada [33,44], Cyprus [34], Iran [35,36 ], Columbia [37], Libya [39], Sweden [40] Asia Pacific [24], Latin America and the Caribbean [25,37], European [26,28,[32][33][34]40], African Region [27,29,30,39], Asia Pacific [31], North America [33,44], Middle East and North Africa [31,35,36] Multilevel 6 Frameworks [45][46][47]…”
Section: Microlevelmentioning
confidence: 99%
“…France [45], Canada [50] European [45], North America [50] The results of the market level analysis (Table 3) indicated that: 50% of the studies applied a macro-level analysis, 31% utilized a meso-level perspective, 14% used a multilevel approach and 5% assessed HIS and HIT from a micro-level lens. The two articles [10,11] that contextualized HIS and HIT evaluation from a micro-level analysis came from the Asia Pacific and European IMIA represented regions [3], whereas meso and macro-level evaluations were dispersed across many diverse IMIA regions [3].…”
Section: Microlevelmentioning
confidence: 99%
See 1 more Smart Citation